2018
DOI: 10.3389/fnagi.2018.00336
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mitochondrial Dynamics in Neurodegenerative Diseases: An Insight Into Prion Diseases

Abstract: Mitochondrial dysfunction is a common and prominent feature of prion diseases and other neurodegenerative disorders. Mitochondria are dynamic organelles that constantly fuse with one another and subsequently break apart. Defective or superfluous mitochondria are usually eliminated by a form of autophagy, referred to as mitophagy, to maintain mitochondrial homeostasis. Mitochondrial dynamics are tightly regulated by processes including fusion and fission. Dysfunction of mitochondrial dynamics can lead to the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 121 publications
0
30
1
Order By: Relevance
“…In mitochondria-stressed cells, damaged mitochondria undergo fragmentation prior to selective mitophagy. 150 , 167 It has been shown that ER–mitochondria contact coordinates mitochondrial division. 168 , 169 Thus, it is tempting to speculate that ER also participates in the intercellular degradation of stressed mitochondria in an unknown manner.…”
Section: Perspectives and Applicationsmentioning
confidence: 99%
“…In mitochondria-stressed cells, damaged mitochondria undergo fragmentation prior to selective mitophagy. 150 , 167 It has been shown that ER–mitochondria contact coordinates mitochondrial division. 168 , 169 Thus, it is tempting to speculate that ER also participates in the intercellular degradation of stressed mitochondria in an unknown manner.…”
Section: Perspectives and Applicationsmentioning
confidence: 99%
“…Neurons are cells of extremely high energy demand and are thus particularly vulnerable to mitochondrial dysfunction. Alterations in the mitochondrial network and consequent mitochondrial dysfunction have been suggested to occur as prominent early features in neurodegenerative diseases [ 90 ]. Nowadays, there is an increasing number of neurodegenerative disorders that are associated with mutations in mitochondrial fusion genes.…”
Section: Mitochondrial Dynamics and Associated Diseasesmentioning
confidence: 99%
“…However, studies analyzing other molecular pathways related to autophagy report an increase of autophagy activity at late stages of the disease. For example, mitochondrial dysfunction is a common and prominent feature of prion diseases ( Zhu et al, 2018 ). Mitophagy, which is the specific autophagic elimination of defective mitochondria, is activated in prion-infected SMB-S15 cells and in mice infected with scrapie strains 139A and ME7 at the terminal stage of the disease, represented by the transcriptional and protein increase of the two essential elements regulating mitophagy activity: PINK1 (PTEN-induced kinase 1) and Parkin ( Gao et al, 2020 ).…”
Section: Autophagy In Prion Diseasesmentioning
confidence: 99%